MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SD NEGERI LAMTEUBEE ACEH BESAR - Trisnawati .; Cut Zahri Harun; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2019)
School will be able to run smoothly if facilities and infrastructure of education very support for learning process. This research uses descriptive method with qualitative approach. The purpose of this research is to describe correctly and real about the management of education facilities and infrastructure in improving the quality of learning in SD Negeri Lamteubee Aceh Besar.Data collection technique include observation, interviews, and documentation studies. Research subjetct were Headmaster, Vice Principal, Teacher Council, and School Staff/Operator. Result of research indicate that: (1) Planning of facilities and infratructure that is with activity analyze first first all school facilities and infrastructure. (2) The procurement of facilities and infrastructure collects inventory data for the data first and knows the inventory. (3) Utilization/use in is used by all citizens of schools, teachers and all school children, utilization of educational inventory should also be effectively monitored by the parties appointed by the school. (4) Maintenance of facilities and infrastructure is needed by teachers and students so that the goods owned by the school is always under supervision and well maintained. (5) Elimination in made a letter of proposal to the Education Office so that related parties can make an official letter for the deletion. Keywords: Management, Infrastructure Education, Improvement of Learning